2008
DOI: 10.1016/j.wasman.2006.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of biodegradation of deinking by-products used as alternative cover material

Abstract: Deinking by-products (DBP) have been used as alternative cover material for landfills and mine tailings. Since DBP is biodegradable because of its high cellulose and hemicellulose content, a laboratory experimental program was performed to monitor the evolution of biodegradation and changes in the physico-chemical and geotechnical properties of DBP samples submitted to accelerated biodegradation for 1460 days at 38 degrees C. The evolution of gas and leachate production was monitored in terms of both quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to the Quebec landfilling regulation, REIMR (Gouvernement du Québec 2009), the seepage control layer must have a saturated hydraulic conductivity of B1.0 E-7 m/s (1.0E-5 cm/s) and a minimum thickness of 0.45 m after compaction. In order to take into account settlement and potential mass loss due to biodegradation (Teixeira 2001;Bédard 2005;Panarotto et al 2005;Aït-Benichou et al 2008), a thickness of 0.60-m was adopted for the DBP layer ). Post-construction monitoring indicated that the actual thickness was 0.63 m.…”
Section: Materials Selectionmentioning
confidence: 99%
“…According to the Quebec landfilling regulation, REIMR (Gouvernement du Québec 2009), the seepage control layer must have a saturated hydraulic conductivity of B1.0 E-7 m/s (1.0E-5 cm/s) and a minimum thickness of 0.45 m after compaction. In order to take into account settlement and potential mass loss due to biodegradation (Teixeira 2001;Bédard 2005;Panarotto et al 2005;Aït-Benichou et al 2008), a thickness of 0.60-m was adopted for the DBP layer ). Post-construction monitoring indicated that the actual thickness was 0.63 m.…”
Section: Materials Selectionmentioning
confidence: 99%
“…Covering with traditional materials will occupy the storage capacity of the landfill and reduce its space for landfill waste. The use of non-traditional materials, namely waste, as covering materials can effectively improve this problem, so it has become a research hotspot in recent years (Narani et al 2020;Ait-Benichou et al 2008;Solan et al 2010). However, the instability of non-traditional materials and the odor reduction effect still need to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…This problem can be overcome if the material being used to perform as a daily landfill cover is sourced from within the waste stream, reducing the landfill void space occupied by virgin soils (Querio and Lundell, 1992) or non waste material. In recent years, much research has been done into finding alternative daily cover (ADC) material, now that traditional materials such as topsoil are not as readily available (Ait-Benichou et al, 2008;Carson, 1992;Querio and Lundell, 1992).…”
Section: Introductionmentioning
confidence: 99%